Narrative and interpretation on Twitter: Reading tweets by telling stories. (September 2018) - Sadler, Neil
Existing research on communication on Twitter has largely ignored the question of how users make sense of the fragmentary tweets with which they are presented. Focusing on the use of Twitter for political reporting in post-revolutionary Egypt, this article argues that the production of mental stories provides readers with a mechanism for interpreting the meaning of individual tweets in terms of their relationships to other material. Drawing on contemporary narratology, it argues that Twitter exhibits key elements of narrativity, but that a creative reading process is nonetheless required to transform this incipient narrativity into coherent, sense-making mental narratives. This foregrounding of the reader's creative role makes stories on Twitter highly fluid and dynamic. Through reference to classic critical theory, I propose that this nonetheless represents an evolution rather than a radical break from earlier forms of narrative reception, which in many cases demanded similarly creative reading practices.